Assessment of antioxidant and xanthine oxidase inhibitory activity of Triadica cochinchinensis stem bark - Carla Wulandari Sabandar; Juriyati Jalil; Norizan Ahmat; Nor-Ashila Aladdin (Institut Teknologi Bandung, 2019)
Triadica cochinchinensis has been used traditionally to treat diseases related to oxidative stress. Nonetheless, little is known about its biological activity. This study aimed to evaluate the antioxidant and xanthine oxidase inhibitory activity of this plant. For this purpose, qualitative phytochemicals, total phenolic, total flavonoid, antioxidant assays (DPPH and FRAP), and xanthine oxidase assay were evaluated towards methanol and organic fractions of its stem bark. Results showed the occurrence of flavonoids, tannins, terpenoids, steroids, and saponins in the methanol extract. The extract and its two fractions (ethyl acetate and methanol) exhibited promising radical scavenging (IC50 values between 3.6-4.5 μg/mL) and ferric reduction activities (4.2-5.5 μg/μg of equivalent trolox amount). They also exhibited inhibition on the xanthine oxidase activity ranging from 43.8 to 80.5% at a dose of 100 μg/mL. These activities could be attributed to the amount of phenolics in the methanol extract and active fractions (136.6-174.1 mg GAE/g of sample). Our results suggested that the methanol extract of T. cochinchinensis stem bark could be used as a promising source of lead molecules for antioxidant and xanthine oxidase inhibitors from natural source.